Colorimetric sensing of uric acid based on sawdust-deposited silver nanoparticles via an eco-friendly and cost-effective approach - Nishan, Umar; Khan, Noaman; Muhammad, Nawshad; Afridi, Saifullah; Badshah, Amir; Shah, Mohibullah; Asad, Muhammad; Ullah, Raheed; Niamat, Haris; Ullah, Riaz; A. Ali, Essam; Ojha, Suvash Chandra (Frontiers in Materials, 2023)
Uric acid is directly linked to gout, arthritis, neurological, cardiovascular, and kidney-related disorders. It is a byproduct obtained from the breakdown of purines and a significant indicator of hyperuricemia observed in both urine and blood. In the absence of any enzyme, it's quite difficult to develop a novel, cost-effective, and clinical method for uric acid detection. Herein, we report a very simple, low-cost, and non-enzymatic method for the selective identification and quantification of uric acid using green synthesized silver nanoparticles (Ag NPs). The desired Ag NPs were synthesized by the hydrothermal method using Erythrina suberosa sawdust as a deagglomeration agent and Psidium guajava extract as a reductant. The synthesis of the sensing platform, i.e., sawdust-deposited Ag NPs, was confirmed through different techniques such as UV-Vis spectrophotometer, FTIR, XRD, EDX, and SEM. Sawdust can offer a good, environmentally friendly, and cost-effective strategy to overcome the problem of agglomeration in nanoparticles. The enzyme mimic, with the help of H2O2, oxidizes the colorless 3,3′,5,5′-tetramethylbenzidine (TMB) to oxidized TMB with a blue-green color. The addition of uric acid reduces the oxidized TMB to a colorless product, resulting in a colorimetric change. For quality improvement, different reaction parameters, including pH, time, TMB, and NPs concentration, were optimized. Our proposed sensor responds in linear ranges of 0.04–0.360 μM, with a limit of quantification of 0.01 μM and a limit of detection of 0.004 μM. The suggested enzyme mimic detected uric acid in blood samples, with particular specificity in the presence of competitive analytes.